The Effect of Brain Tumors on BOLD Functional MR Imaging Activation in the Adjacent Motor Cortex: Implications for Image-guided Neurosurgery - Holodny, Andrei I.; Schulder, Michael; Liu, Wen-Ching; Wolko, Jonathan; Maldjian, Joseph A.; Kalnin, Andrew J. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Functional MR (fMR) imaging data coregistered to a neurosurgical navigation system have been proposed as guides for the resection of brain tumor in or adjacent to eloquent cortices. The purpose of this study was to compare data obtained from the side of the brain affected by tumor with the contralateral side and to determine if there are physiological limitations of fMR imaging in accurately determining the location of the primary motor cortex.METHODS: Ten patients with tumors in or directly adjacent to the motor cortex were studied with fMR imaging (finger-tapping paradigm). fMR imaging data were analyzed using multiple R values. These data were coregistered to a real-time intraoperative neurosurgical navigation system.RESULTS: Significant variability of motor cortex activation patterns was noted among individual patients. The activation volumes on the side of the tumor were significantly smaller compared with the contralateral side for all tumors not previously resected (0.66±0.47). This was most pronounced in glioblastomas (0.27±0.21). We propose that these differences were caused by a loss of autoregulation in the tumor vasculature of glioblastomas and venous effects.CONCLUSION: Notwithstanding the differences noted, the motor cortex was identified successfully in all patients. This was confirmed by intraoperative physiological identification of the motor cortex and a lack of postoperative neurologic deficit.